Evaluation of Anti-Mullerian Hormone Levels, Antral Follicle Counts, and Mean Ovarian Volumes in Chemotherapy-Induced Amenorrhea among Breast Cancer Patients: A Prospective Clinical Study - Çağlar Ünal; Çetin Ordu; Tolga Özmen; Ahmet Serkan İlgun; Filiz Çelebi; Bülent Baysal; Enver Özkurt; Tomris Duymaz; Zeynep Erdoğan İyigün; Sevgi Kurt; Mehmet Alper Öztürk; Kezban Nur Pilancı; et al. (Current Oncology, 2023)
Estradiol (E2), a follicle-stimulating hormone (FSH), AMH, and inhibin B levels, along with AFC and MOV, are used to determine ovarian reserve in pre-menopausal women. Studies have shown that AMH levels are more sensitive than those of E2, FSH, and inhibin B and that AFC and MOV can be used to evaluate ovarian reserve. AMH, AFC, and MOV measurements were performed before and after adjuvant SC in 3-month periods for one year. Patients were classified as experiencing chemotherapy-induced amenorrhea (CIA) if they did not have menstrual cycles for a period of six months or longer following the conclusion of their chemotherapy treatment. We aimed to evaluate the factors affecting chemotherapy-induced amenorrhea in breast cancer patients treated with adjuvant chemotherapy and the performance of baseline measurements of AMH, AFC, and MOV to predict chemotherapy-induced amenorrhea. The effects of different chemotherapy regimens on the AMH level, AFC, and MOV in CIA patients were investigated. Seventy-one patients were eligible for this study, and the median age was 38 years (range: 23–45). The median follow-up was 37 months (range: 20–51), and CIA developed in 62% of the patients. The AMH level and AFC were significantly decreased one year after SC (p < 0.0001), whereas MOV was not (p = 0.507). AMH levels before chemotherapy (median: 1.520 vs. 0.755, p = 0.001) and at the end of the first year (median: 0.073 vs. 0.010, p = 0.030) and pre-treatment AFC (median: 12 vs. 4.50, p = 0.026) were lower in patients with CIA compared to those without CIA. The AMH levels before SC were the most valuable and earliest factor for predicting CIA development. In addition, there was no difference between the chemotherapy regimens (including or not including taxane) in terms of CIA development.